Morfometri Kepiting Bakau (Scylla spp.) di Kawasan Hutan Mangrove Muara Sungai Mutusan Kabupaten Sambas - Ari Hepi Yanti, Aris Susilo, Tri Rima Setyawati (Universitas Tanjungpura, 2017)
Scylla spp. live in association with the mangrove forest. A damaged or loss of mangrove forest ecosystems will affect the mangrove crab population. This research aims to determine the types, morphometry and characteristics of mangrove crabs in the mangrove forest of Mutusan Estuary, Sambas Regency. The research was carried out from April to June 2015. The research obtained two species i.e., S. paramamosain and S. serrata. The species S. paramamosain has an average weight (W) of 138.13 g with an average carapace width (CW) of 95.42 mm, an average frontal margin width (FMW) of 27.97 mm and an average chela length (CL) of 57.45 mm. The species S. serrata has an average weight (W) of 212.82 g with a carapace width (CW) of 205.14 mm, an average frontal margin width (FMW) of 28.42 mm and an average length of chela (CL) of 67.11 mm. Based on the size of carapace width (CW), the Scyla spp. of young phase dominates the mangrove crab population in the mangrove forests of Mutusan Estuary, Sambas Regency.